Can long range mechanical interaction between drugs and membrane proteins define the notion of molecular promiscuity? Application to P-glycoprotein-mediated multidrug resistance (MDR) - Rauch, Cyril; Paine, Stuart W.; Littlewood, Peter (Biochimica et biophysica acta, 2013)
Failure of treatment in over 90% of patients with metastatic cancer is due to acquired MDR. P-glycoprotein (Pgp) remains the archetypal drug membrane transporter expressed in many MDR cancer cells. Albeit the ATPase activity of Pgp is triggered by the presence of drug in the membrane, it is commonly assumed that when two drug molecules meet the same Pgp the protein cannot handle them efficiently due to steric effects and as a result the ATPase activity drops. However it is also possible that drug accumulating in the lipid-phase may affect the membrane in such a way that it imposes the mechanical closure of transporters by opposing the force mediated by ATP consumption. In this context, long range interactions between drug and membrane proteins could exist. Recent data concerning Pgp structure have allowed us to formalize this hypothesis and we present a physico-mathematical model that is not based on predictive QSAR or other empirical methods applied to experimental data. Long range mechanical interactions between Pgp and drugs are predicted to occur at an external concentration of drug ~10–100μM as previously determined experimentally at which concentration ~50% of transporters should be rendered inactive. Distance interaction(s) between Pgp and drugs exist explaining an ill-defined effect concerning the ability of any drug to inhibit Pgp once a threshold concentration in the membrane has been reached. Potential application of the theory in the field of pharmacology concentrating on the notion of molecular promiscuity and toxicity in drug discovery prediction is discussed. •Drug physicochemical properties dictate the interaction with the cell membrane.•Drug-membrane interaction changes the physical properties of the cell membrane.•Changes in the physical properties of the cell membrane impact on membrane proteins.•Drug-induced changes in the physical properties of the cell membrane freeze Pgp activity.•Freezing Pgp activity via physical changes of the membrane defines molecular promiscuity.